City Consciousness from Colonial Calcutta in Bal Krishna Sama’s Mukunda Indira - Adhikari, Chulendra (NPRC Journal of Multidisciplinary Research, 2025)
Background: Bal Krishna Sama's Mukunda Indira (1937) scrutinizes the interplay between the urban modernity of colonial Calcutta and the formation of Mukunda’s metropolitan consciousness. This paper focuses on Mukunda's psychological and cultural shift that profoundly contributes to Mukunda's emotional detachment from deep-rooted cultural heritage in the Indian metropolis of colonial Calcutta, which functions as a fractured space in stark contrast to Kathmandu which serves as a space for traditional sociocultural resistance.Methods: This study draws on qualitative and analytical data pooled from primary texts, aligning with the concept of Georg Simmel's urban sociological theory, as discussed in The Metropolis and the Mental Life (1903), to provide a theoretical framework for comprehending Mukunda's emotional crisis, fragmented psyche, and rising consciousness.Result: The study reveals that Mukunda’s colonial experience in the Indian metropolis is examined through his psychological alienation, cultural and emotional dislocation, fragmentation, and over-stimulation, which aligns with Simmel’s metropolitan type of individuality. Conclusion: Sama’s Mukunda Indira makes a critical engagement with the colonial modernity of Calcutta, which works not merely as a backdrop but as an ever-evolving and changing force shaping the ideological consciousness of the protagonist, rooted in the British colonial legacy and grounded in Simmel’s urban sociological theory.Novelty: The novelty of this article lies in its interdisciplinary approach, which foregrounds the city as an active force in shaping colonial subjectivity, providing new insights into Nepali literary criticism.